2021
DOI: 10.1101/2021.03.08.434156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allopregnanolone mediates affective switching through modulation of oscillatory states in the basolateral amygdala

Abstract: Brexanolone (allopregnanolone), was recently approved by the FDA for the treatment of post-partum depression, demonstrating long-lasting antidepressant effects. Despite our understanding of the mechanism of action of neurosteroids as positive allosteric modulators (PAMs) of GABAA receptors, we still do not fully understand how allopregnanolone exerts these persistent antidepressant effects. We demonstrate that allopregnanolone and similar synthetic neuroactive steroid analogs, SGE-516 (tool-compound) and zuran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(49 citation statements)
references
References 28 publications
5
44
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted April 19, 2021. ; https://doi.org/10. 1101/2021 To confirm that the Gq-DREADD-induced IPSC bursts were mediated by the excitation of PV interneurons through Gq signaling, we blocked Gq protein activation with a selective Gα q/11 inhibitor YM-254890 (10 µM), which blocks the switch of Gα q from the GDP-to GTP-bound state (Takasaki et al, 2004). We found that CNO-induced IPSC bursts were completely eliminated with the Gq blocker (Fig.…”
Section: Figurementioning
confidence: 76%
See 2 more Smart Citations
“…The copyright holder for this preprint (which this version posted April 19, 2021. ; https://doi.org/10. 1101/2021 To confirm that the Gq-DREADD-induced IPSC bursts were mediated by the excitation of PV interneurons through Gq signaling, we blocked Gq protein activation with a selective Gα q/11 inhibitor YM-254890 (10 µM), which blocks the switch of Gα q from the GDP-to GTP-bound state (Takasaki et al, 2004). We found that CNO-induced IPSC bursts were completely eliminated with the Gq blocker (Fig.…”
Section: Figurementioning
confidence: 76%
“…Parvalbumin interneurons are critically involved in the generation of gamma-frequency oscillations in the cortex and hippocampus (Bartos et al, 2007;Buzsáki et al, 2012;Cardin et al, 2009;Hájos et al, 2004;Sohal et al, 2009). Mechanistic studies in these structures indicate that tonic PV neuron activity provides inhibitory signaling to principal neurons that drives the local gamma rhythm, demonstrated by phase locking of PV neuron activity to the gamma cycle (Bartos et al, 2007;Hájos et al, 2004) and by optogenetic activation and inhibition of PV neuron activity (Antonoudiou et al, 2021;Cardin et al, 2009;Sohal et al, 2009). Like in cortical structures, PV interneurons in the BLA densely target the perisomatic region of principal neurons to modulate amygdalar output (Davis et al, 2017;Ozawa et al, 2020;Vereczki et al, 2016;Veres et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LFP recordings were performed as previously described (Antonoudiou et al, 2021) in male and female C57BL/6J and Gabrd -/mice after a week of recovery from implant surgery. LFP recordings were acquired using Lab Chart software (AD Instruments) collected at 4 KHz and amplified 100X.…”
Section: Lfp Recordingsmentioning
confidence: 99%
“…LFP recordings were acquired using Lab Chart software (AD Instruments) collected at 4 KHz and amplified 100X. The data were band pass filtered (1-300 Hz) and spectral analysis was performed in MATLAB (Antonoudiou et al, 2021) using MatWAND (https://github.com/pantelisantonoudiou/MatWAND) which utilizes the fast Fourier transform similar to previous reports (Kruse and Eckhorn, 1996;Frigo and Johnson, 1998;Pape et al, 1998;Freeman et al, 2000). Briefly, recordings were divided into 5 second overlapping segments and the power spectral density for a range of frequencies was obtained (Oppenheim et al, 1999).…”
Section: Lfp Recordingsmentioning
confidence: 99%